(untitled) (Research, Society and Development, 2021)
The entomopathogenic fungus Metarhizium rileyi is known as a biological control agent for several lepidopterans, among which the Noctuidae family stands out. The objective of this work was to evaluate the effect of fungicides on the development of two isolates of M. rileyi under laboratory conditions. The in vitro effect of five fungicides on the UFMS 06 and UFMS 07 isolates of the fungus M. rileyi was studied. The products were placed in Petri dishes containing the Potato-Dextrose-Agar (BDA) culture medium, in the concentrations recommended for the application of the product in the field. After incubating the fungus in the culture medium, the plates were sealed with PVC film and placed in an air-conditioned chamber (type BOD) at 25 ± 1 °C, relative humidity of 70 ± 10% and a photoperiod of 12 hours for a period of 7 days, mycelial growth and spore concentration were evaluated. To quantify the germination percentage, a suspension of 1.0 × 106 con.mL-1 was used, being kept at rest for two hours in the different fungicides. Right after this period, 1.0 mL of the suspension was plated with the aid of a graduated pipette (1mL) in Petri dishes and spread with a Drigalsky loop in the nutrient medium, after inoculation the plates were identified and sealed with PVC film, and incubated for 20 hours in an air-conditioned BOD chamber at 25 ± 1 °C, relative humidity of 70 ± 10% and photoperiod of 12 hours. The fungicides tested in this work all interfered in the vegetative growth, in the production of conidia and in the germination of the two isolates of the fungus, in the biological index test all products were classified as toxic.